The Mathematics Model Analysis of Distribution Concentration of Total Suspended Solid in Gresik Coastal Coast with Landsat 8 Satellite Imagery - Hendrata Wibisana; Novie Handajani; Primasari Cahya Wardhani (Nusantara Science and Technology Proceedings)
Total suspended solid is one of the useful parameters to detect the turbidity level that occurs in the body of water. The concentration distribution from total suspended solid is an activity that is quite interesting to study especially in the coastal areas, knowing the distribution value of total suspended solids, it is possible to know the change of ecosystem. The Ujung Pangkah Gresik is an area chosen as an example to determine the distribution concentration of total suspended solid value by making an appropriate mathematical model that can imagine the condition of the body of water in that coastal area. Thus, the purpose of this study was to investigate the mathematics model analysis to imagine the distribution concentration of total suspended solids. The method to model this is by remote sensing that was used in Landsat 8 satellite imagery. In addition, this study used the remote sensing method on the visible light canal (red, green, and blue) to determine the mathematics model analysis of total suspended concentration distribution. The result showed that there was red canal has significant image result compared to another visible canal. The red canal result showed the mathematics model exponential with correlation value R 0.873 has a significant effect to image the total suspended solids concentration distribution. This study concludes that Landsat 8 satellite image can quite effectively and accurately be used to map the distribution of total suspended solid especially in the shallow water environment adjacent to ponds and estuary.